The Effect of Different Planting Times on the Agricultural Characters of Some Safflower Cultivars Planted in Elazig Ecological Conditions - Ayışığı, Samet; Karaaslan, Davut (My University, 2024)
This study was carried out in 2021-2022 and 2022-2023 growing seasons to determine the yield and some yield characteristics of different safflower cultivars at different planting times in Elazig ecological conditions. The planting dates were 25 October, 10 November and 25 November in both years and Dincer, Linas, Olas and Zirkon cultivars were used. Among the agricultural traits examined in this study, winter resistance rate ranged from 4.58-100 %, flower yield ranged from 143.55-508.25 mg plant-1, plant height ranged from 51.90-82.04 cm, number of lateral branches ranged from 1.71-5.50 pcs plant-1, number of heads ranged from 3.20-10.01 pcs plant-1, head diameter ranged from 15.91-24.43 mm, thousand seed weight ranged from 33.73-46.17 g, and seed yield ranged from 23.74-160.96 kg da-1. In Elazig ecological conditions, it was determined that safflower, which is generally planted as summer safflower, can also be grown as winter safflower, although early sowing causes too much plant loss, planting can be done between 10 November and 30 November, and Dincer and Zirkon varieties came to the fore in this study.
Keywords: Cultivar; safflower; Elazig; planting time